Does Nissen fundoplication improve deglutition in children? - Soyer, Tutku; Yalçın, Şule; Demir, Numan; Karhan, Asuman Nur; Saltık-Temizel, İnci Nur; Demir, Hülya; Tanyel, Feridun Cahit (The Turkish Journal of Pediatrics, 2017)
A prospective study was performed to evaluate the effect of Nissen fundoplication (NF) on deglutition in children. Children who underwent NF between 2011-2015 were evaluated for demographic features, clinical findings, diagnostic methods for gastroesophageal reflux (GER) and indications for NF. Penetration aspiration scale (PAS), functional oral intake scale (FOIS) and esophageal functions were evaluated by videoflouroscopy (VFS). Preoperative and postoperative VFS findings were compared to evaluate the effect of NF on clinical findings and deglutition. Twenty-three children with a mean age of 5.08 ± 3.7 years were included. Female to male ratio was 15:8. Recurrent respiratory infections (RTI) (n: 14, 60.8%), swallowing dysfunction (n:13, 56.5%) and vomiting (n:10, 43.4%) were the most common symptoms. Preoperatively GER was diagnosed with barium swallowing study (BSS) contrast graphs (n:20, 87%) and with 24-hour esophageal pH monitorization (n:8, 34.8%). In 39.1% of patients, medical treatment for GER was used with a mean duration of 8 ± 5.8 months. Indications for NF were swallowing dysfunction (n: 18, 78%), GER complications (n:6, 26%), associated anatomical problems (n:4, 17.3%) and unresponsiveness to medical treatment (n: 3, 13%). Postoperative barium swallowing study and 24-hour esophageal pH monitorization showed no GER after NF in 95% of patients. Number of RTI were significantly decreased after NF (preoperative vs postoperative infection rate 4.21 vs 1.6 respectively, p < 0.05). VFS findings showed that PAS was significantly decreased after NF during both liquid and semi-liquid swallowing (p < 0.05). After NF, upper esophageal opening (UEO) was decreased when compared to preoperative VFS findings (p < 0.05 Esophageal cleaning, esophageal motility, esophageal backflow and lower esophageal sphincter narrowing did not alter after NF (p > 0.05). FOIS were significantly improved after NF (p < 0.05). VFS findings showed that penetration and aspiration were significantly decreased after NF and children had less RTI. Although, esophageal motility evaluated by VFS did not changed after NF, functional oral intake significantly improved in children.
Keywords: Nissen fundoplication; deglutition; dysphagia; gastroesophageal reflux